Design thinking and shared ignorance as a framework for student-faculty partnerships: A case study of the creation of teaching activities for wicked problems - Bolstad, Torstein; Strømberg, Anders; Amberg, Sven; Bjørnevik, Ida (International Journal for Students as Partners, 2024)
This case study describes and discusses how student-faculty partnerships can be strengthened through design thinking and the establishment of shared ignorance, i.e., an awareness of how none of the involved parties understands the problem or knows the optimum solution of the partnership project. As a case, we use a student-faculty project that aimed to develop course material for an electrical engineering course based on project work involving wicked problems. This project illustrates, through student and faculty reflections, how design thinking and shared ignorance can be used to subvert implicit power structures and strengthen the partnership and project outcomes.